Parameter analysis in the optimization of concrete beams using the algorithm Colony of Fireflies (Research, Society and Development, 2022)
There are many ways in the literature to optimize structures using a wide range of algorithms, however the use of bioinspired algorithms for structures is still little explored. Given this context, this article demand to verify, using the bioinspired algorithm Colony of Fireflies, the parameters for the optimization of three variables of the construction process of a beam through the reduction of its objective functions, giving, in the end, its production cost per linear meter. Several parameter values were analyzed to arrive at those that best suited the proposed objective. The results obtained showed evidence of the robustness of the algorithm, reaching convergence to a value very close to the ideal after few iterations. Its relevance and potential use for much more robust construction elements is clear.